METTL14-mediated epitranscriptome modification of MN1 mRNA promote tumorigenicity and all-trans-retinoic acid resistance in osteosarcoma - Hong-Bo Li; Gang Huang; Jian Tu; Dong-Ming Lv; Qing-Lin Jin; Jun-Kai Chen; Yu-Tong Zou; Dung-Fang Lee; Jing-Nan Shen; Xian-Biao Xie (EBioMedicine, 2022)
Summary: Background: Osteosarcoma (OS) is the most common primary malignant bone tumor in adolescents. The molecular mechanism behind OS progression and metastasis remains poorly understood, which limits the effectiveness of current therapies. RNA N6-methyladenosine (m6A) modification plays a critical role in influencing RNA fate. However, the biological significance of m6A modification and its potential regulatory mechanisms in the development of OS remain unclear. Methods: Liquid chromatography-tandem mass spectrometry (LC-MS/MS), dot blotting, and colorimetric ELISA were used to detect m6A levels. Western blotting, quantitative real-time PCR (RT-qPCR) and immunohistochemistry (IHC) were used to investigate METTL14 expression levels. Methylated RNA immunoprecipitation sequencing (MeRIP-seq) and transcriptomic RNA sequencing (RNA-seq) were used to screen the target genes of METTL14. RNA pull-down and RNA immunoprecipitation (RIP) assays were conducted to explore the specific binding of target genes and relevant m6A “readers”. RNA stability and polysome analysis assays were used to detect the half-lives and translation efficiencies of the downstream genes of METTL14. IHC and clinical data were applied to explore the clinical correlations of METTL14 and its downstream target genes with the prognosis of OS. Findings: We observed the abundance of m6A modifications in OS and revealed that METTL14 plays an oncogenic role in facilitating OS progression. MeRIP-seq and RNA-seq revealed that MN1 is a downstream gene of METTL14. MN1 contributes to tumor progression and all-trans-retinoic acid (ATRA) chemotherapy resistance in OS. Mechanistically, MN1 is methylated by METTL14, specifically in the coding sequence (CDS) regions, and this modification is recognized by the specific m6A reader insulin-like growth factor 2 mRNA binding protein 2 (IGF2BP2) to prevent MN1 mRNA degradation and promote it translation efficiency. IHC showed that MN1 expression was positively correlated with METTL14 and IGF2BP2 expression in OS tissues. The METTL14-IGF2BP2-MN1 panel demonstrated more promising prognostic value for OS patients than any of these molecules individually. Interpretation: Our study revealed that METTL14 contributes to OS progression and ATRA resistance as an m6A RNA methylase by regulating the stability and translation efficiency of MN1 and thus provides both an underlying biomarker panel for prognosis prediction in OS patients. Funding: This work was supported by the National Natural Science Foundation of China (Grants 81972510 and 81772864).